Systematic Literature Review: Meningkatkan Sikap Percaya Diri Anak Usia 4-6 Tahun Melalui Tari Kreasi - Sri Sumarni; Rina Rahayu Siregar; Nia Paramita; Sari Mufidah; Rike Anggraini; Dea Tri Astian (Indonesian Journal of Elementary and Childhood Education, 2023)
There are still many children who lack self-confidence. The phenomenon of lack of self-confidence in children today is that they are full of fear and want to always be close to their surroundings. This research article aims to examine various creative dance references to increase or stimulate the self-confidence of children aged 4-6 years. This study is based on the results of article analysis from 2019-2023, various national and international articles. The sciencedirect keywords are creative dance, self-confidence, children's social-emotional, while the Googlescholar keywords are self-confidence, creative dance, children's social-emotional. The results of this research found that there were 12 articles that were analyzed and stated that creative dance was able to increase the self-confidence of children aged 4-6 years. It can be concluded that creative dance can increase children's self-confidence by carrying out it according to the implementation steps that will be chosen.